A twinning initiative between midwife associations in Ghana and Sweden -A process evaluation study - Hanna Fjellström; Emelie Sandberg; Johanna Blomgren; Malin Grahn; Fredrica Hanson; Netta Ackon; Gifty Baidoo; Louise Nordström; Malin Bogren (Global Health Action)
Background This study describes the evaluation of a twinning initiative between the Ghana Register Midwives Association and the Swedish Association of Midwives. Recognising the importance of midwives being supported by a national midwife association, the initiative was to strengthen the professional association in Ghana as a labour union and to inspire Swedish midwives to involve themselves in international work. Objective The study aimed to evaluate a twinning initiative between the Ghana Registered Midwives Association and the Swedish Association of Midwives. Method Two focus group discussions and four individual interviews were held with nine midwives from the Ghana Registered Midwives Association (n = 6) and the Swedish Association of Midwives (n = 3). The interviews and analysis were guided by a process evaluation framework using content analysis. Results The twinning initiative was successfully implemented regarding fidelity, dose, and reach, despite adaptations to the original project plan. Both associations gained visibility, with the Ghana Registered Midwives Association growing its paid membership by 97%, from 631 to 1,245 members during the twinning initiative. The results suggest that the Swedish Association of Midwives enhanced its understanding of international midwifery, promoted knowledge exchange, and raised awareness of midwives’ global roles in improving care. Conclusion The Ghana Registered Midwives Association and the Swedish Association of Midwives had a positive experience with the twinning initiative, despite deviations from the original plan. Midwives from both associations benefitted from sharing best practices and mutual support in their roles as newly formed labour trade unions. These findings could benefit other midwife associations in future twinning initiatives.